1997
DOI: 10.1111/j.1600-0838.1997.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

The aging tendon

Abstract: The aging tendon Tuite DJ, Renstrom PAFH, O'Brien M. The aging tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 34 publications
2
98
0
6
Order By: Relevance
“…Intrinsic factors such as the quality of collagen as well as the crosssection of tendons decrease over time in the aging process [21][22][23][24], although there is controversy about this, others have suggested that with the advanced age the tendon is shown stronger and more rigid [25], the truth is that with our work the control group experienced a slight decrease in tendon linear stiffness. There are little studies that have done research on the effect of food supplementation on the tendon biomechanics; however a study with rats concluded that a supplementation of 3% of glycine and lysine added to the diet increased the stiffness of the tendon of the rats tail significantly compared to a control group fed with a standard diet [26].…”
Section: Resultsmentioning
confidence: 39%
“…Intrinsic factors such as the quality of collagen as well as the crosssection of tendons decrease over time in the aging process [21][22][23][24], although there is controversy about this, others have suggested that with the advanced age the tendon is shown stronger and more rigid [25], the truth is that with our work the control group experienced a slight decrease in tendon linear stiffness. There are little studies that have done research on the effect of food supplementation on the tendon biomechanics; however a study with rats concluded that a supplementation of 3% of glycine and lysine added to the diet increased the stiffness of the tendon of the rats tail significantly compared to a control group fed with a standard diet [26].…”
Section: Resultsmentioning
confidence: 39%
“…In most cases the wavy arrangement of fibers seen in healthy tendons is disturbed, possibly as a result of cumulative effect of microinjuries occurring throughout patients life [57]. This is accompanied by poorer tissue hydration, decreased content of proteoglycans and glycoproteins and increased lipid storage within the tendon [2,57]. Reduced perfusion due to a diminished number of capillaries is also observed and neovascularization process is usually absent [18].…”
Section: Ageing Of the Tendonsmentioning
confidence: 99%
“…This includes thickening of collagen fibers ad disintegration of their hierarchical structure [18]. In most cases the wavy arrangement of fibers seen in healthy tendons is disturbed, possibly as a result of cumulative effect of microinjuries occurring throughout patients life [57]. This is accompanied by poorer tissue hydration, decreased content of proteoglycans and glycoproteins and increased lipid storage within the tendon [2,57].…”
Section: Ageing Of the Tendonsmentioning
confidence: 99%
See 2 more Smart Citations